Transanal protrusion of intussusceptions in children - Ezomike Uchechukwu Obiora; Ekenze Sebastian Okwuchukwu; Igwilo Innocent Ogundu (Wolters Kluwer Medknow Publications, 2014)
Background: The aim of the following study is to report our management experience and outcome of transanal protrusion of intussusceptions. Patients and Methods: Retrospective analysis of all cases of intussusceptions protruding through the anal opening from January 2008 to June 2013. Results: Of 62 cases of intussusceptions, transanal protrusion occurred in 10 patients (16% anal protrusion rate) with a male:female ratio of 2:3. They were aged 4-96 months (mean 22.6 ± 30.7, median 7.5 months). Six were infants while four were above 1 year. Duration of symptoms ranged from 2 to 14 days (mean 5.9 days ± 3.4) with only two patients presenting within 48 h. Clinical features included vomiting (100%), abdominal pains (100%), bloody mucoid stool (100%), abdominal distension (90%), and palpable left iliac fossa mass (70%). Three patients had preceding diarrhoea (30%) and two had preceding upper respiratory tract infection (20%). Duration of hospital stay ranged from 5 to 23 days (mean 12 days ± 5.6). Findings at surgery included seven ileocolic and two colocolic intussusceptions (one patient died before surgery). Operative procedures were right hemicolectomy (5), operative manual reduction (3), left hemicolectomy (1) giving a 67% bowel resection rate. One patient died giving a 10% mortality rate. Conclusion: Transanal protrusion occurred more in females and is associated with late presentation, older age, high bowel resection rate, and high mortality.